Correlates of death among SARS-CoV-2 positive veterans: The contribution of lifetime tobacco use. (February 2021) - Raines, Amanda M.; Tock, Jamie L.; McGrew, Shelby J.; Ennis, Chelsea R.; Derania, Jessa; Jardak, Christina L.; Lim, Jennifer H.; Boffa, Joseph W.; Houtsma, Claire; Jones, Kenneth R.; Martin-Klinger, Caitlin; Widmer, Kyle; et al.
Highlights: Examined factors that contribute to likelihood of death among veterans with COVID-19. Retrospective chart reviews were conducted on 440 SARS-CoV-2 positive veterans. Older age and male gender increased risk of death. Further, immunodeficiency, endocrine, and pulmonary diseases increased risk of death. Notably, lifetime tobacco use predicted veteran mortality above and beyond these variables. Abstract: Despite a growing body of research examining correlates and consequences of COVID-19, few findings have been published among military veterans. This limitation is particularly concerning as preliminary data indicate that veterans may experience a higher rate of mortality compared to their civilian counterparts. One factor that may contribute to increased rates of death among veterans with COVID-19 is tobacco use. Indeed, findings from a recent meta-analysis highlight the association between lifetime smoking status and COVID-19 progression to more severe or critical conditions including death. Notably, prevalence rates of tobacco use are higher among veterans than civilians. Thus, the purpose of the current study was to examine demographic and medical variables that may contribute to likelihood of death among veterans testing positive for SARS-CoV-2. Additionally, we examined the unique influence of lifetime tobacco use on veteran mortality when added to the complete model. Retrospective chart reviews were conducted on 440 veterans (80.5% African American/Black) who tested positive for SARS-CoV-2 (7.3% deceased) at a large, southeastern Veterans Affairs (VA) hospital between March 11, 2020 and April 23, 2020, with data analysis occurring from May 26, 2020 to June 5, 2020. Older age, male gender, immunodeficiency, endocrine, and pulmonary diseases were positively related to the relative risk of death among SARS-CoV-2 positive veterans, with lifetime tobacco use predicting veteran mortality above and beyond these variables. Findings highlight the importance of assessing for lifetime tobacco use among SARS-CoV-2 positive patients and the relative importance of lifetime tobacco use as a risk factor for increased mortality.